Inclusive Leadership and Innovative Performance: A Multi-Level Mediation Model of Psychological Safety - Li, Tong; Tang, Ningyu (Frontiers in Psychology, 2022)
Taking both individual and team levels into consideration has been called for years in terms of researches on leadership. Inclusive leadership, a trending leadership style emerging from the global needs of managing the increasingly diversified workplace nowadays, has yet been rarely studied at both levels. To answer these calls, we specifically analyze the relationship between inclusive leadership, team psychological safety, and innovative performance via multilevel analysis. Results are based on a study of 356 employees from 90 working teams. Individual perceptions of inclusive leadership are positively related to individual innovative performance through the mediation of individual psychological safety; Team perceptions of inclusive leadership are positively related to team innovative performance through the mediation of team psychological safety. What’s more, team perceptions of inclusive leadership positively relate to individual innovative performance through the cross-level mediation of individual psychological safety. Implications for both theory and practice are discussed.